Division behaviours and their effects on pre‐implantation development of pig embryos. Issue 9 (16th June 2022) - Tao, Ruixin; Bi, Jiaying; Zhu, Fuquan; Wang, Xuguang; Jia, Chao; Xu, Hongxia; He, Xu; Li, Juan
Abstract: The quality of pre‐implantation embryos could affect developmental efficiency after embryo transfer. However, the assessment of pre‐implantation embryos was unsatisfactory, especially in pig embryos to date. Therefore, this study was designed to investigate available and applicable parameters that indicate developmental potential and quality of porcine pre‐implantation embryos produced by handmade cloning (HMC), and parthenogenetic activation without zona pellucida (PAZF) and with zona pellucida (PAZI). Firstly, a common division behaviour was detected, that is the formation of uneven division with two unequal size blastomeres (UD 2‐cell), especially in HMC embryos; then, the proportion of UD 2‐cell was found to be significantly higher than that of even division with equal size blastomeres (ED 2‐cell) (72.56 ± 4.56 vs. 24.57 ± 1.92). The formation of UD 2‐cell might be due to the spindle migration along the long axis in 1‐cell stage, and the cleavage furrow was not formed in the centre of cytoplasm. In the two sister blastomeres of UD 2‐cell, uneven distribution of organelles (mitochondria and lipid droplet) was observed with lower proportion in the smaller one ( p  < .05). Although no difference in blastocyst rate was observed between UD and ED 2‐cell embryos, the cell number per blastocyst from UD 2‐cell embryos was lower than that from ED 2‐cell embryos (44.15 ± 2.05 vs. 51.55 ± 1.83). Besides, because of non‐synchronized division of each blastomere, the following three cleavage routes were observed in all HMC/PAZF/PAZI embryos: T1 (2‐cell → 3‐cell → 4‐cell → ≥5‐cell → morula → blastocyst), T2 (2‐cell → 3‐cell → 4‐cell → morula → blastocyst) and T3 (2‐cell → 3‐cell/4‐cell → morula → blastocyst). Therefore, in pig in vitro‐produced embryos, division behaviours of uneven volume of cytoplasm and non‐synchronized cell cycles were observed at the early embryonic developmental stage, which might be another potential factor to evaluate embryonic development.